Pemerataan Akses Pendidikan Bagi Anak Putus Sekolah di Provinsi Nusa Tenggara Barat - I Nyoman Wijana; Muhamad Suhardi (Journal Of Administration and Educational Management (ALIGNMENT), 2018)
This study aims to reveal, explain, and describe the social reality that occurred in West Nusa Tenggara, namely the expansion and equitable access to education for abandoned children. The research was conducted using a qualitative approach, by phenomenology method. The results of this study indicate that access to education for abandoned children in West Nusa Tenggara is very low. Conclusion, From the aspect of the availability of facilities facilitated by the Provincial Government, there is only one orphanage that handles abandoned children education, located in a provincial city serving ten districts. From the aspect of affordability, abandoned children find it difficult to reach the education provided by the government, caused by poverty, and the distance between cities in West Nusa Tenggara. Keywords: Expansion, Equity, Access to Education, Child Dropouts